Probing Noncovalent Interaction Strengths of Host‐Guest Complexes Using Negative Ion Photoelectron Spectroscopy - Sun, Haitao; Sun, Zhenrong; Wang, Xue‐Bin (Chemistry : a European journal, 2024)
Noncovalent interactions (NCIs) are crucial for the formation and stability of host‐guest complexes, which have wide‐ranging implications across various fields, including biology, chemistry, materials science, pharmaceuticals, and environmental science. However, since NCIs are relatively weak and sensitive to bulk perturbation, direct and accurate measurement of their absolute strength has always been a significant challenge. This concept article aims to demonstrate the gas‐phase electrospray ionization (ESI)‐negative ion photoelectron spectroscopy (NIPES) as a direct and precise technique to measure the absolute interaction strength, probe nature of NCIs, and reveal the electronic structural information for host‐guest complexes. Our recent studies in investigating various host‐guest complexes that involve various types of NCIs such as anion–π, (di)hydrogen bonding, charge‐separated ionic interactions, are overviewed. Finally, a summary and outlook are provided for this field. Noncovalent interactions (NCIs) are the driving forces for the formation and stability of host‐guest complexes that ubiquitously exist in fields as diverse of biology, chemistry, materials sciences, pharmaceuticals, and environmental ion separations. Now the absolute interaction strength of NCIs can be directly and precisely measured by gas‐phase electrospray ionization negative ion photoelectron spectroscopy.